P093 COVID-19 lockdown and mental health burden in Inflammatory Bowel Disease paediatric patients: a case-control study. (27th May 2021) - Milo, F; Romeo, E F; Rea, F; Grimaldi Capitello, T; De Angelis, P; Tabarini, P
Abstract: Background: From March 10 to May 3, 2020, Coronavirus disease 2019 (COVID-19) and subsequent enforced lockdown in Italy has led to an increased general psychological distress 1 . In particular, people with both compromised immune function and pre-existing physical or psychiatric problems are at increased risk of adverse psychosocial outcomes 2 . The purpose of this study was to compare mental health burden in Inflammatory Bowel Disease (IBD) paediatric patients with and without COVID-19 lockdown exposure. Methods: We conducted a retrospective case-control study comparing mental health outcomes of two matched 1:1 IBD paediatric groups: Group 1 - before the exposure (January 2019-September 2019) and Group 2 - after COVID-19 pandemic lockdown (April 2020-December 2020). Matching criteria included gender, age, disease duration, IBD subtype, Body Mass Index and disease activity (remission or active). This study included patients with Crohn Disease (CD) and Ulcerative Colitis (UC), >12 years, attending outpatient visits at Bambino Gesù Children Hospital. Data were collected using the Generalised Anxiety Disorder (GAD-7) for anxiety and the Patient Health Questionnaire (PHQ-9) for depression. We have estimated the prevalence of anxiety and depression between the two groups. Both groups were also compared with respect to the average score of anxiety and depression symptoms. Sociodemographic and clinical data were recorded from patients' medical chart. Results: A total of 108 IBD paediatric patients (62 males, 54 with CD and 54 with UC, mean age=16±2, 5 years) was enrolled in this study. Out of these, 54 patients were enrolled in Group 1 and 54 in Group 2. Using a cut-off score ≥10, we found similar prevalence of anxiety (13.0% vs 22.2%, P=.206) and depression (13.0% vs 18.5%, P=.428) among the groups. Average scores were quite similar among the two groups, both for anxiety (5.78 vs 5.96, P=.924) and depression (5.89 vs 5.87, P=. 704). Symptom severity levels were mild (≃6) in both groups, according to standardized instrument cut-offs. No significant associations were found between disease activity and symptoms of anxiety and depression in both groups. Conclusion: IBD-related symptoms (i.e. weight loss, persistent diarrhoea, abdominal pain and fatigue) lead to severe psychosocial impairment in paediatric IBD patients. COVID-19 pandemic outbreak and enforced isolation (i.e., lockdown, long distance learning, and social restrictions) limited patients' stressful social situations engagement and paradoxically prevented a worsening of their mental health. References: -Gualano MR et al., Int J Environ Res Public Health. 2020;17(13):4779. -Druss BG, JAMA Psychiatry 2020; 77: 891–92.